Layer by layer self-assembled hybrid thin films of Porphyrin/Polyoxometalates@Pt nanoparticles for photo & electrochemical application. (June 2022) - Zang, Dejin; Huo, Zhaohui; Yang, Shu; Li, Qi; Dai, Guoyong; Zeng, Mengyan; Ruhlmann, Laurent; Wei, Yongge
Abstract: Organic-inorganic hybrid films [TTMAP/Zn4 P4 W30 @Pt]n and [TTMAP/Ti12 P8 W60 @Pt]n were fabricated via Layer by Layer self-assembly on ITO from water-soluble meso -tetrakis(4- N, N, N -trimethylaminophenyl)porphyrin (TTMAP) and polyoxometalates (POM) stabilized platinum nanoparticles. The obtained composites POMs@Pt NPs and the hybrid thin films [TTMAP/POMs@Pt]n have been characterized by UV–vis spectroscopy, X-ray photoelectron spectroscopy, atomic force microscopy, quartz crystal microbalance and electrochemistry for their formation behaviour, structure composition and photo/electrochemical properties which endow them great application potential in economical energy conversion catalysis including hydrogen evolution and photocurrent generation. Under near neutral aqueous conditions, HER activity and high stability were achieved by drastically decreasing Pt loading down to 1.97 wt% with [TTMAP/Ti12 P8 W60 @Pt]n and 8.50 wt% with [TTMAP/Zn4 P4 W30 @Pt]n compared to 20 wt% Pt/C, respectively. Furthermore, photocurrent generation was improved by up to 33 % with Pt NPs loading compared to [TTMAP/POMs]n thin films. The present organic-inorganic hybrid thin film based energy conversion strategies provides a huge potential and promising approach to have low-cost hydrogen and solar energy industries. Graphical Abstact: Organic-inorganic hybrid films composed of polyoxometalate stabilized platinum nanoparticles and porphyrin are prepared via LBL method which offers promising strategies toward economical energy conversion catalysis including hydrogen evaluation and photocurrent generation. ga1 Highlights: POMs stabilized Pt NPs was synthesized under UV light. POMs`s intrinsic properties control the morphologies of POM@Pt NPs. The dynamic formation of TTMAP/POM@Pt hybrid films was investigated by UV-Vis spectroscopy and QCM measurements. Promising photo & electrochemical application potential was validated.